Reversible Optical and Electrical Switching of Air‐Stable OFETs for Nonvolatile Multi‐Level Memories and Logic Gates. (27th October 2015) - Qian, Yan; Li, Wenwen; Li, Wen; Xu, Xiuxia; Lin, Zongqiong; Xie, Linghai; Yi, Mingdong; Huang, Wei
Abstract : Air‐stable multi‐bit and reversible nonvolatile memories of photochromophore‐based organic field‐effect transistors (OFETs) are realized using independent light or electric modulation. The distinct current states can be obtained independently by either voltage or light programming and are highly stable in ambient atmosphere with retention time over 10 4 s.